Initiatives and Challenges of Agricultural Cooperatives in Advancing the Sustainable Development Goals: Evidence from Region I, Philippines - Tablang, Solomon; Bitoniov, Josefina; Toledo, Ralph Rendell (JPAIR Multidisciplinary Research, 2026)
Agricultural cooperatives are recognized as important institutional actors in advancing the United Nations Sustainable Development Goals (SDGs), particularly in rural and agrarian economies. This study examined the initiatives, services, and challenges of agricultural cooperatives in relation to SDG implementation in Region I of the Philippines. A mixed-methods research design was employed, combining structured surveys of officers from 30 medium and large agricultural cooperatives with selected semi-structured interviews to contextualize the quantitative findings. Descriptive statistics and cross-tabulations were used to analyze cooperative profiles, services, SDG-aligned initiatives, and governance, environmental, and market-related challenges. Findings show that most cooperatives are medium-sized, long-established, and moderately capitalized organizations with lean staffing structures. Their services are primarily concentrated on credit provision, commodity distribution, and agricultural input facilitation, while higher-value activities such as processing, mechanization, and diversified production remain less common. Cooperatives demonstrate strong engagement in SDGs related to poverty reduction, food security, decent work, and partnerships through fair pricing, microfinance, training, and collaboration with government and private institutions. However, these contributions are constrained by governance limitations, financial constraints, climate-related risks, and market competition. Medium-sized cooperatives experience greater vulnerabilities in governance, environmental pressures, and market access, while larger cooperatives face more bureaucratic and administrative constraints. The study highlights the need for profile-sensitive interventions that strengthen governance systems, expand access to finance and markets, and support investment in climate-smart and value-adding technologies. Greater integration of environmental sustainability into cooperative operations is also necessary to enhance the contribution of agricultural cooperatives to inclusive and sustainable rural development and to the achievement of the SDGs.
Keywords: Agricultural cooperatives; Sustainable Development Goals; Rural development; Sustainability practices; Philippines